MENGUKUR TINGKAT MOTIVASI MASYARAKAT TERHADAP PEMANFAATAN PEKARANGAN UNTUK PERTANIAN PERKOTAAN DI KOTA YOGYAKARTA - Defira Suci Gusfarina; Irham Irham (Universitas Gadjah Mada, 2019)
Urban agriculture continues to grow in relation to environmental, economic, health and social issues, including in the city of Yogyakarta. The people of Yogyakarta City use the yard to grow vegetables and fruit. The economic, social, cultural, and psychological conditions of each household vary to be able to implement an innovation. In order to achieve sustainable yard utilization, the utilization of the yard must adjust to the motivation of the community. The purpose of this study is to determine the level of environmental, economic, health and social motivation of the community in utilizing the yard for farming. This study uses descriptive research methods with qualitative approaches and survey techniques using a questionnaire on 113 respondents. Motivation is measured using Likert scale from item statements. Each statement is given a score of 1 to 5 according to the answers provided. These answers are calculated, made into percentage and an interval scales is used as the reference for high, medium and low category. The results showed that the motivation of the people of Yogyakarta City sequentially from high to low were health motivation, environmental motivation, social/community motivation and economic motivation. Agricultural planning and policy in cities, especially in the yard, must pay special attention to multifunctional farming practices that are environmentally friendly as suppliers of healthy food for families, become a recreation area and a place for socializing and selfdevelopment so that leisure time become more productive.